Prospects for the application of underwater image restoration methods to facilitate marine geological exploration - I.V. Semernik; A.A. Taraseko; K.V. Samonova (Компьютерная оптика)
This paper provides an overview of modern methods for underwater image restoration and enhancement, as well as an analysis of advantages and disadvantages of the methods when used for the imagery obtained during deep-sea geological exploration. Due to the fact that the main criteria for choosing a processing method are precisely the accuracy and reliability of underwater image restoration, rather than speed and improved frame perception, it seems most appropriate to choose methods based on the traditional approach and using a priori information about environmental conditions and the relative position of the camera and the underwater object, received from the underwater vehicle sensors.